EKSPLORASI POLA PEMBELAJARAN BERBASIS DIFERENSIASI: STUDI KOMPARATIF ANTARA SDN 15 PARIT BINTANG DAN SDN 05 SUNGAI PADUAN - Tutin Darisa; Sholehuddin (STKIP Subang, 2026)
This study aims to explore and compare the patterns of implementing differentiated instruction in two elementary schools, namely SDN 15 Parit Bintang and SDN 05 Sungai Paduan. The background of this research is based on the demands of 21st-century education, which require learning to be adaptive to the diverse characteristics of students. This study employed a qualitative approach with a descriptive comparative design. Data were collected through participant observation, semi-structured interviews, and document analysis, involving school principals and teachers as participants. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the implementation of differentiated instruction at SDN 05 Sungai Paduan is more systematic and integrated compared to SDN 15 Parit Bintang. SDN 05 Sungai Paduan has implemented diagnostic assessment, a variety of instructional strategies, differentiation of process and product, as well as continuous formative assessment. In contrast, SDN 15 Parit Bintang still demonstrates partial implementation, characterized by uniform learning practices, limited mapping of students’ needs, and less varied use of strategies and learning media. These findings indicate that the success of differentiated instruction is highly influenced by teachers’ pedagogical readiness and the support of the school system. Therefore, strengthening teacher competencies and institutional support is necessary to create adaptive, inclusive, and student-centered learning.